Analytical Study of Violence Theme in Victoria Schwab’s This Savage Song - Muntazar Mehdi (University of Chitral Journal of Linguistics and Literature, 2019)
This research article focuses on the theme of violence and its representation bythe characters of the novel “This Savage Song” by Victoria Schwab. Howviolence is transmitted through genes to next generations and to what extentsocio- psycho factors are involved in it, has also been discussed. Similarly, inwhat manner violent events and deeds by the parents affect the psychology ofchildren and how it inculcates aggressive behaviour in their minds has beenstudied. What role is played by the parents in grooming the personality ofchildren and ultimately their decisions to choose the right or wrong way hasbeen argued. In the light of the theory of Judith Harris, this research paperhighlights all the phenomena involved: How the social hierarchy controls thebehaviour. In addition, the aggressive approach of the people in their lives hasbeen analyzed in the light of the study of second theorist Thomas W Blume. Asthe novel is a unique representation of supernatural characters, the monsters,which are the products of some cruel deeds, this research paper brings outdifferent dimensions of human sufferings with respect to these supernaturalbeings. Moreover, the researcher also discusses that, in what manner the curseof violence creates an inevitable vicious cycle of cruel monsters that makes thelife of the characters turbulent and miserable.